If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -19)(x + 12) = 0 Reorder the terms: (-19 + x)(x + 12) = 0 Reorder the terms: (-19 + x)(12 + x) = 0 Multiply (-19 + x) * (12 + x) (-19(12 + x) + x(12 + x)) = 0 ((12 * -19 + x * -19) + x(12 + x)) = 0 ((-228 + -19x) + x(12 + x)) = 0 (-228 + -19x + (12 * x + x * x)) = 0 (-228 + -19x + (12x + x2)) = 0 Combine like terms: -19x + 12x = -7x (-228 + -7x + x2) = 0 Solving -228 + -7x + x2 = 0 Solving for variable 'x'. Factor a trinomial. (-12 + -1x)(19 + -1x) = 0Subproblem 1
Set the factor '(-12 + -1x)' equal to zero and attempt to solve: Simplifying -12 + -1x = 0 Solving -12 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + -1x = 0 + 12 Combine like terms: -12 + 12 = 0 0 + -1x = 0 + 12 -1x = 0 + 12 Combine like terms: 0 + 12 = 12 -1x = 12 Divide each side by '-1'. x = -12 Simplifying x = -12Subproblem 2
Set the factor '(19 + -1x)' equal to zero and attempt to solve: Simplifying 19 + -1x = 0 Solving 19 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-19' to each side of the equation. 19 + -19 + -1x = 0 + -19 Combine like terms: 19 + -19 = 0 0 + -1x = 0 + -19 -1x = 0 + -19 Combine like terms: 0 + -19 = -19 -1x = -19 Divide each side by '-1'. x = 19 Simplifying x = 19Solution
x = {-12, 19}
| 36m^2-21m^3-49n^2+343n^3= | | (4x-1)/3=5 | | -3x+3=18 | | 4x-1/3=5 | | -18-3=6-7x | | 9(f-2)=2(f+3) | | 6+2Y=12 | | -12x-20=40 | | 9=-5x+29 | | 4(x+7)+3x-14= | | -2m+4=4 | | -18=3(x-5) | | -2m+4=-4 | | 3x-9=4x-13 | | y-21.2=-2.3 | | s(t)=-5600t+67200 | | x^2-18x+11=0 | | 6A+6+1(7A+-1)=0 | | 3x-(2x+6)=6x-(x-6) | | -7x+6=-x+42 | | 3x^2-35=0 | | (3z-8)=(z+4) | | 6(d-2)=5(d-1) | | -x(6y^3-5xy^2+x^2y-5x^3)= | | 6x+8=11x-3 | | 2r+20=55-3r | | 3.4x-2.6-x=16.6 | | 0.05x+0.12(x+5000)= | | 4.27x+4=18.2329+2x | | y=-10+3x | | 15x=6(4+2x) | | 4x^2-25x+47=3x+2 |